URGENSI LANDASAN MORAL DALAM PRAKTIK PENDIDIKAN: STUDI MIXED METHOD TERHADAP PERSEPSI GURU DAN IMPLEMENTASI NILAI KARAKTER DI SEKOLAH - Dwinova Indhira Putri; Sofyan Sauri; Fitri Dwi Indriyani (STKIP Subang, 2025)
The moral degradation crisis in contemporary educational institutions demands systematic strengthening of character education implementation. This study aims to explore teachers' perceptions of the urgency of moral foundations in educational practice and identify patterns of character value implementation in schools. The research method uses a mixed method design with a sequential explanatory design approach. Research participants consisted of 45 students and one classroom teacher at SDN Tunas Jaya. The quantitative phase uses a structured questionnaire with a Likert scale, while the qualitative phase uses semi-structured interviews and participatory observation. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through thematic analysis. The research results show that 90% of teachers believe in their crucial role as moral agents with dominant strategies in the form of behavioral exemplary (95%), habituation of religious activities (85%), and positive verbal reinforcement (80%). Religious values become the highest priority (95%), followed by honesty (90%) and responsibility (85%). The main challenges include limited learning time and minimal parental participation. Systematic implementation resulted in a significant increase in student character with task responsibility increasing 22%, discipline and politeness each 20%. The study concludes that teachers' positive perceptions become the foundation for effective character value implementation through consistent exemplary strategies.